PURCHASE DECISION PADA CANVA PRO: PERAN PERCEIVED VALUE DAN CUSTOMER EXPERIENCE MELALUI CUSTOMER SATISFACTION PADA KALANGAN GEN Z DI SIDOARJO - Zainiyah, Alfidhotul; Novie, Muhafidhah; Muzdalifah, Laily; Kamila, Edita Rachma (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
Purpose: This study aims to analyze the effect of Perceived Value and Customer Experience on Purchase Decision through Customer Satisfaction as a mediating variable among Gen Z users of Canva Pro in Sidoarjo. Methods: A quantitative approach was employed using a survey method, with data collected from 170 respondents selected through purposive sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Analysis Data: The research utilized outer model analysis to test validity and reliability, followed by inner model analysis to examine the direct and indirect effects among variables. Results Discussion: The findings reveal that Perceived Value and Customer Experience significantly influence Purchase Decision, both directly and indirectly through Customer Satisfaction. The most dominant indicators are Service Quality for Perceived Value and Outcomes Focus for Customer Experience. Conclusion: This study confirms the role of Customer Satisfaction as a partial mediator between Perceived Value, Customer Experience, and Purchase Decision. Practically, Canva should enhance service quality and customer experience to increase user satisfaction and encourage subscription conversions.